2003
DOI: 10.1046/j.1570-7458.2003.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific differences in oak foliage affect preference and performance of gypsy moth caterpillars

Abstract: The gypsy moth, Lymantria dispar (L.) (Lepidoptera: Lymantriidae), is an introduced defoliator that preferentially feeds on oaks, Quercus spp. (Fagaceae) in the northeastern USA. As the gypsy moth expands its geographic range, the extensive oak component in forests and urban environments of the USA assure its successful establishment. Given their economic and ecological importance, and the gypsy moth's potential to cause mortality, we evaluated caterpillar preference and performance on various oaks prevalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
3
38
1
Order By: Relevance
“…It has been suggested that phenotypic traits that affect arthropod communities as phenology, physical defenses, and foliar chemistry are features that have a genetic basis (Johnson and Agrawal 2005;Bangert et al 2006) but have only rarely been linked to both plant genetics and arthropod community structure (Wimp et al 2007). Also, these attributes can vary between host-plant species (Foss and Rieske 2003;Forkner et al 2004;Marquis and Lill 2010), affecting both the quantity and quality of resources available to arthropods (Murakami et al 2007). Understanding the strength of these associations is important as they provide a mechanistic approach to comprehend the relationship between plant genetic diversity, environment, and arthropod community structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that phenotypic traits that affect arthropod communities as phenology, physical defenses, and foliar chemistry are features that have a genetic basis (Johnson and Agrawal 2005;Bangert et al 2006) but have only rarely been linked to both plant genetics and arthropod community structure (Wimp et al 2007). Also, these attributes can vary between host-plant species (Foss and Rieske 2003;Forkner et al 2004;Marquis and Lill 2010), affecting both the quantity and quality of resources available to arthropods (Murakami et al 2007). Understanding the strength of these associations is important as they provide a mechanistic approach to comprehend the relationship between plant genetic diversity, environment, and arthropod community structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some oaks accumulate high levels of hydrolyzable tannin (bur, pin, or willow) while other species (cherrybark, Northern red) accumulate far smaller amounts (Foss and Rieske, 2003), suggesting an overall genetic constraint on the total quantity of hydrolyzable tannin that can be produced. Within that limit, both simple phenolics and complex ellagitannins are accumulated in patterns that are genetically controlled (Yarnes et al, 2006), with distinct tannin chemotypes identified in a population of Quercus gambelii x Q. grisea (Yarnes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Oak foliar tannins vary spatially (Crawley and Akhteruzzaman, 1988), temporally (Feeny and Bostock, 1968;Makkar et al, 1991), and in response to changing light and disturbance regimes (Kruger and Reich, 1997;Rieske, 2001, 2003;Rieske, 2002). Herbivore suitability, including abundance (Hunter, 1993), preference (Foss and Rieske, 2003), and performance (Valentine et al, 1983;Bourchier and Nealis, 1993), have been linked to oak foliar tannin concentrations.…”
Section: Introductionmentioning
confidence: 99%